AB0184 Diagnostic impact in the clinical setting of nailfold vieocapillaroscopy on connective diseases. (12th June 2018) - Soleto, C.; Torrens, L.; Nieto González, J.C.; ,; Anzola, Ana M.; Rocío Caballero Motta, Liz.; García, Leticia.; Plaza, María Correyero.; González Benítez, D.D.D.; Benavente, Belén Serrano.; Barrio, Julia Martínez.; López-Longo, Javier.; et al.
Abstract : Background: Nailfold video-capillaroscopy (NVC) is a non-invasive technique that allows visualisation of structure and distribution of capillaries at the nailfold level 1, altered somehow in some connective diseases, specially in the Scleroderma (Scl) disease spectrum. The main indication of this technique is the investigation of Raynaud's phenomenon (RF). Objectives: Our objective is to investigate the diagnostic impact of NVC in the daily clinical practice. Methods: The design is an observational, longitudinal, retrospective and descriptive study, which included patients with at least one NVC between June 2012 and December 2016 from our Rheumatology register of patients. We collected demographic data (age, gender, indication, autoantibodies, etc.), number of explorations performed and their result. We also collected in a dichotomist fashion if the NVC contributed in the diagnostic workup, between one consultation and the other after the NVC realisation. Results: 437 patients were included with a total of 637 explorations. Of these 437 patients, 115 (24.1%) had a second NVC, 39 (8.2%) a third one, 9 (1.9%) a fourth and only two with a fifth NVC (both with diagnostic of Scl). We noticed a diagnostic change between the first consultation and the next one in 35 cases (5.49%). In 14/35 (40%) of these cases, the NVC played an important role in the diagnostic change, with changes in the NVC pattern, from normal or unspecific to Scl pattern (table 1). These changes, occurred after the first NVC in 10 patients (71.4%), 3 (21.4%) after the second, and 1 (7.1%) after the third exploration in addition of new disease manifestations, diagnostic tests and other image techniques. Of these 14 patients, 100% had positive ANA, 5 (35.7%) Anticentromere Antibodies (Ab), 1 (7.1%) anti-Ro Ab and 1 (7.1) Antiphospholipid Ab. Conclusions: The NVC in our centre had a limited but important impact in the diagnostic process of connective diseases. This impact was specially relevant in patients diagnosed with Scleroderma. The probability of having a diagnostic change diminishes with successive explorations. Reference: [1] Cutolo M, Pizzorni C, Secchi ME, Sulli A. Capillaroscopy. Best Pract Res Clin Rheumatol2008Dec;22(6):1093–108. Disclosure of Interest: None declared